The influence of clinical risk factors on the classification of human cancer-associated fibroblasts in PDAC and pancreatitis patients - Viktoria Boeker; Lena Wilke; Ana Mansourkiaei; Van Manh H. Le; Kaira A. Church; Zoltan Czigany; Bo Kong; Fernanda G. Kugeratski; Jörg Kleeff; Jürgen Weitz; Christoph Kahlert (BJC Reports)
Abstract Cancer-associated fibroblasts (CAFs) constitute an important cell population in the microenvironment of pancreatic cancer. They can arise from disease-associated fibroblasts (DAFs) to support or restrain tumor growth. How many CAF subtypes exist and what signals drive their development is unclear. Currently, there are three commonly accepted subtypes, namely myofibroblast-like (myCAF), immunomodulatory (iCAF), and antigen-presenting (apCAF). Here, we analyzed the correlation between clinical risk factors with the proportion of each CAF subtype. In our patient cohort (n = 21), we investigated DAFs from patients with chronic pancreatitis (CP) and CAFs from pancreatic ductal adenocarcinoma (PDAC) patients after surgical resection via flow cytometry and RNA expression analysis. The expression of iCAF marker Interleukin-6 displayed significant differences depending on lifestyle factors, such as smoking status, age, and Body Mass Index (BMI). The apCAF marker HLA-DQA1 correlated with age. The largest difference showed the quantitative difference of apCAF markers in ~40% of PDAC- and ~20% of CP patients. In conclusion, clinical risk factors may influence the prevelance of specific CAF subsets. Unraveling the complex interplay between CAFs and tumor cells is crucial for novel therapies to improve long-term survival for pancreatic cancer patients.